RANCANG BANGUN SISTEM PERAMALAN PENJUALAN ES KRIM DENGAN METODE DOUBLE EXPONENTIAL SMOOTHING (STUDI KASUS :CV ALDY ABADI JAYA, MUARA WAHAU) - Viramadita Arthamia Putri; Sentot Achmadi; Ali Mahmudi (SKANIKA: Sistem Komputer dan Teknik Informatika, 2026)
The ice cream sales agent CV Aldy Abadi Jaya in Muara Wahau faces challenges in forecasting daily fluctuating ice cream demand. Inaccurate stock estimation often leads to excess or shortage of inventory, requiring an effective strategy to balance supply and demand. This study aims to design and develop a web-based sales forecasting system using the Double Exponential Smoothing (DES) method. This method was chosen because it can provide accurate predictions for data with a trend pattern. The research utilizes historical sales data of ice cream from CV Aldy Abadi Jaya. The system was developed using the Laravel framework and MySQL database. It automatically performs sales forecasting calculations and displays the results through an interactive dashboard that helps users interpret prediction outcomes easily. The results show an accuracy level and Mean Absolute Percentage Error (MAPE) value of 13,83%, indicating that the Double Exponential Smoothing method can generate reliable forecasts for future sales. The developed system is expected to help the company plan stock more effectively, reduce the risk of losses, and improve efficiency in the ice cream distribution process..